The Role of Teachers in Shaping the Disciplinary Character of Fifth-Grade Students at SD Negeri 141 Pekanbaru - Ririza Maulina; Leny Julia Lingga (The Future of Education Journal, 2025)
This study aims to describe the role of teachers in shaping the disciplinary character of fifth-grade students at SD Negeri 141 Pekanbaru through a qualitative case study approach. The research was conducted to address the need for understanding how teachers contribute to the development of students’ discipline in both academic and non-academic aspects. Data were collected through observations, interviews, and documentation to obtain a comprehensive picture of teacher practices in fostering discipline. The findings reveal that teachers play a crucial role in building students’ disciplinary character through six main dimensions. First, teachers act as role models by demonstrating proper appearance and polite communication, providing students with concrete examples of daily discipline. Second, teachers serve as motivators who encourage students to follow school rules and complete assignments on time, thereby fostering responsibility and self-awareness. Third, teachers function as evaluators who respond to student behavior and guide them in understanding the consequences of their actions. Fourth, teachers influence student attendance through supervision, guidance, and communication with parents to ensure students attend regularly and avoid truancy. Fifth, teachers support punctuality by modeling timely behavior and guiding students to submit tasks within deadlines. Sixth, teachers foster rule compliance by teaching students to follow school regulations and maintain respectful interactions with teachers and peers. Overall, the study concludes that teachers at SD Negeri 141 Pekanbaru play a significant role not only in delivering knowledge but also in shaping disciplinary character through consistent example, motivation, evaluation, and collaboration with parents and the school environment.